Relationship between love for knowledge, excellent Muslim personality and human transformation capital: a model built with structural equation measurement (SEM) - Syaidatun Nazirah Abu Zahrin,; Nazneen Ismail,; Nur Hidayah Abd Malek,; Mashitoh Yaacob,; Fazilah Idris, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The concept of love for knowledge is very relevant in building a great civilization. It is not only relevant, but should be given a serious emphasis because ilmu (knowledge) and amal (practice) are the core of human excellence. The purpose of the study was to model out the relationship between love for knowledge, excellent Muslim personality and Human transformation capital. The study was conducted on 767 students of the Institute of Higher Education around the Klang Valley, Malaysia. Structural Equation Modeling Analysis has been used for the purpose of identifying the role of human transformation capital as a mediator in determining the relationship between love for knowledge and excellent Muslim personality. The results of the analysis show that there was a significant positive relationship between love for knowledge and the excellent Muslims. While the transformation of human capital was found to function significantly as a partial mediator between love for knowledge and excellent Muslims. In other words, love for knowledge will affect the excellent Muslims and transform the human capital. It is recommended that these three important aspects become the fundamental values of success to develop a greater Islamic civilization.